Learning vocabulary in another language - Nation, I. S. P. (Cambridge, United Kingdom Cambridge University Press, 2022)
"Now in its third edition, this book provides an engaging, authoritative guide to the teaching and learning of vocabulary in another language. It contains descriptions of numerous vocabulary-learning strategies, which are supported by reference to experimental research, case studies, and teaching experience. It also describes what vocabulary learners need to know to be effective language users. This new edition has been updated to incorporate the wealth of research that has come out of the past decade. It also includes a new chapter on out-of-classroom learning, which explores the effect of the Internet and electronic resources on learning. This vital resource for all vocabulary researchers shows hat by taking a systematic approach to vocabulary learning, teachers can make the best use of class time and help learners get the best return for their learning effort. "-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Language and languages -- Study and teaching; Vocabulary -- Study and teaching